2011
DOI: 10.1007/s12571-010-0099-7
|View full text |Cite
|
Sign up to set email alerts
|

The potential of small-scale rainfed agriculture to strengthen food security in Arab countries

Abstract: In most Arab countries, domestic agricultural production is insufficient. The gap between production and demand is likely to increase due to climate change and other factors. This review paper examines the challenges and possible solutions to ensuring food security in the future. It focuses on rainfed agriculture, which accounts for two-thirds of the region's cropland, the bulk of its food staples, and almost all its rangelands. Given the scarcity of water and arable land, there are few opportunities in the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 13 publications
0
12
0
Order By: Relevance
“…The land-use conversion has been an important factor in the total anthropogenic emissions with an attendant increase in radiative forcing. The gap between agronomic production and food demand, already affecting more than one billion people, is likely to increase by the projected climate change, especially so in marginal areas such as in the Arab countries [28].…”
Section: Climate Change and World Soilsmentioning
confidence: 99%
“…The land-use conversion has been an important factor in the total anthropogenic emissions with an attendant increase in radiative forcing. The gap between agronomic production and food demand, already affecting more than one billion people, is likely to increase by the projected climate change, especially so in marginal areas such as in the Arab countries [28].…”
Section: Climate Change and World Soilsmentioning
confidence: 99%
“…The overwhelming majority of agricultural producers are asset-poor smallholders who use simple technologies (hand hoes and oxen) and cultivation practices (low agricultural input practices) and are characterised by low productivity, limited capital, and vulnerability to natural and man-made changes (Haddad et al, 2011). Their agricultural activities are mainly dependent on unpredicted rainfall, and their practice in using irrigation is very limited (Olesen & Bindi, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…In China, irrigation income has enabled rural farm households to send children to school, buy groceries for the family, visit relatives in distant areas, and afford mobile phones (Huang et al, 2006). Makombe and Sampath (1999), Kamara et al (2002), Mati (2008) and Haddad et al (2011) reported similar findings.…”
Section: Livelihood Status Of Respondentsmentioning
confidence: 84%
“…This increased the cropping frequency to two/three times a year, and also increased the farm yield. Furthermore, farmers could switch from low-to high-value production, in this way realizing more income and assets (Haddad et al, 2011;Fanadzo, 2012;Kuwornu and Owusu, 2012).…”
Section: Introductionmentioning
confidence: 99%